Effectiveness of Student's Critical Thinking Skill with Problem-Based Learning (PBL), Osborn Model and Integration of PBL-Osborn - Saputra, Moch Dwi Irsyad; Alimah, M.Pd, Dr. Siti; Setiati, M.Si, Dr. Ning (Journal of Innovative Science Education, 2019)
This research aims to analyze the effectiveness of the application of the Problem Based Learning (PBL), Osborn and PBL-Osborn Integration on students' critical thinking skill. This research used posttest only comparison group design with a total sampling technique of 3 classes. Class VIII A using the PBL, class VIII B using the Osborn model and class VIII C using integration of PBL-Osborn models. The data analysis technique used the One Way Analysis of Variance (ANOVA) test to determine differences between the experimental classes. The results of the ANOVA test showed significant differences among the three learning models towards students' critical thinking skill in the human digestive system. To find out the class pairs that are significantly different using the Least Significant Difference (LSD) test. The LSD Test results show that class VIII B-VIII C pairs have a significant difference. The class VIII A-VIII B pairs and VIII A-VIII C pairs have no significant differences. Based on the results of the LSD analysis, the conclusion of this research is the integration of PBL-Osborn learning model is more effective than the osborn model